Udder morphology, milk production and udder health in small ruminants - Vrdoljak, Josip, inženjer agronomije (Array, 2020)
In recent years there has been an increasing trend in research of sheep and goat udder morphology, not only from the view of its suitability for machine milking, but also in terms of milk yield and mammary gland health. More precisely, herds consisting of high-yielding sheep and goats as a result of long-term and one-sided selection to increase milk yield, have been characterised by distortion of the udder morphology caused by increasing the pressure of udder weight on its suspensory system. Along with the deteriorated milking traits, which is negatively reflected on the udder health, some udder morphology traits are often emphasized as factor of production longevity of dairy sheep and goats. Since the intention of farmers and breeders nowadays is to increase the milk yield of sheep and goats while maintaining desirable udder morphology and udder health, the aim of this paper is to give a detailed overview of the current knowledge about the relationship of morphological udder traits with milk yield, and the health of the mammary gland of sheep and goats. External measures of udder size (circumference, width and depth of the udder) are strongly correlated with milk production in sheep and goats. The morphological udder traits determining its suitability for machine milking (such as teat position and teat angle, udder depth, teat size, cistern height) are related to the mammary gland health in sheep and goats. Thus, the incidence of mastitis is noticeably higher in the udders of unsuitable shape for machine milking (deep and hung udders, unfavourable position of teats, etc.). Consequently, the morphological udder traits that affect the milkability of sheep and goats are indirectly related to milk yield.